Stability of beta-titanium T-loop springs preactivated by gradual curvature - Caldas, Sergei Godeiro Fernandes Rabelo (2017)
ABSTRACTObjective:Evaluate changes in the force system of T-Loop Springs (TLS) preactivated by curvature, due to stress relaxation.Methods: Ninety TLSs measuring 6 x 10 mm, produced out with 0.017 x 0.025-in TMA® wire and preactived by gradual curvature, were randomly distributed into nine groups according to time point of evaluation. Group 1 was tested immediately after spring preactivation and stress relief, by trial activation. The other eight groups were tested after 24, 48 and 72 hours, 1, 2, 4, 8 and 12 weeks, respectively. Using a moment transducer coupled to a digital extensometer indicator adapted to a universal testing machine, the amount of horizontal force, moment and moment-to-force ratios were recorded at every 0.5 mm of deactivation from 5 mm of the initial activation, in an interbracket distance of 23 mm.Results: The horizontal forces decreased gradually among the groups (p< 0.001) and the moments showed a significant and slow decrease over time among the groups (p< 0.001). All groups produced similar M/F ratios (p= 0.532), with no influence of time.Conclusions: The TLSs preactivated by curvature suffered a gradual deformation over time, which affected the force system, specifically the moments, which affected the horizontal forces produced.